Analysis of Students’ Misconceptions about the Earth and Its Changes Using a Three-Tier Test - Mutiara Putri, Sheryl Mutiara Putri; Kurnia, Budi (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2025)
This study aims to analyze elementary school students’ misconceptions about the Earth and its changes using a three-tier diagnostic instrument. An accurate understanding of Earth's phenomena is very important for students to build a foundation of scientific thinking from an early age. However, in reality, many students hold incorrect initial conceptions that continue over time, leading to misconceptions that are difficult to detect through conventional tests. For this reason, this study employed a survey method with a mixed quantitative and qualitative approach to identify the patterns and depth of students’ misconceptions. The research participants consisted of 38 sixth-grade students from one elementary school in Sukabumi Regency. Data were collected using 10 items of a three-tier diagnostic instrument that included answer choices, levels of confidence, and students’ conceptual reasoning. The analysis indicated that students experienced various misconceptions across several sub-concepts of Earth and its changes, with an average percentage of misconceptions reaching 56%. These findings indicate that most students have not yet developed a comprehensive scientific understanding of these natural phenomena. Therefore, it can be concluded that the three-tier diagnostic instrument is effective for identifying and analyzing students’ misconceptions and can serve as an important reference for teachers in designing Natural Science learning strategies that are more meaningful and oriented toward conceptual understanding